2018
DOI: 10.1192/bjp.2018.216
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry does need more randomised controlled trials

Abstract: Edited by Kiriakos Xenitidis and Colin Campbell Contents ▪ Psychiatry does need more randomised controlled trials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The other paper frequently referred to as a 'landmark' in the decline of insulin coma therapy (Burns, 2019) is the report of a randomized controlled trial carried out by Brian Ackner and colleagues at the Maudsley, Bethlem and Cane Hill Hospitals in London and Surrey and published in 1957. The study compared insulin coma therapy with a barbiturate-induced coma using random allocation and was one of the first randomized controlled trials in psychiatry (Ackner et al, 1957).…”
Section: The Decline Of Insulin 1953-65mentioning
confidence: 99%
See 2 more Smart Citations
“…The other paper frequently referred to as a 'landmark' in the decline of insulin coma therapy (Burns, 2019) is the report of a randomized controlled trial carried out by Brian Ackner and colleagues at the Maudsley, Bethlem and Cane Hill Hospitals in London and Surrey and published in 1957. The study compared insulin coma therapy with a barbiturate-induced coma using random allocation and was one of the first randomized controlled trials in psychiatry (Ackner et al, 1957).…”
Section: The Decline Of Insulin 1953-65mentioning
confidence: 99%
“…The consensus view is that insulin coma therapy, like other ineffective treatments, was discarded with the advent of modern research techniques and a new understanding of what constitutes proper and reliable evidence. Most authors credit the randomized controlled trials, published in the late 1950s, with having disproved the idea that insulin coma therapy was effective (Burns, 2019;James, 1992), especially the trial that compared it with a barbiturate-induced coma and found no difference in outcome (Ackner, Harris and Oldham, 1957). For some, it marks the start of the movement towards 'evidence based medicine' because it was the first therapy to be rejected on the basis of randomized controlled trials (Andrews, Briggs, Porter, Tucker and Waddington, 1997;Burns, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation